Pertanggungjawaban Pidana Korporasi Terhadap Pencemaran Lingkungan Hidup Ditinjau dari Undang-undang Cipta Kerja - Kadek Dicky Candra Mahendra; I Nyoman Gede Sugiartha; Luh Putu Suryani (Jurnal Interpretasi Hukum, 2021)
Human activities that are less controlled, make a clean and healthy living environment less and less, this is because the earth is currently getting older and the activities of humans themselves are not properly preserving the environment. Humans have a role and responsibility to empower the environment to maintain the ecosystem. However, the current reality is that most environmental crimes often involve corporations. This study aims to examine the regulation of criminal acts by corporations in the perspective of the Copyright Act and to reveal criminal sanctions against corporations that commit acts of environmental pollution in terms of the Copyright Act. This research uses a normative research type, with a Legislative approach. As for what is used as primary data, namely Law Number 32 of 2009, Law Number 11 of 2020 concerning Job Creation is the legal basis for knowing criminal arrangements and criminal sanctions against corporate criminal liability for environmental pollution in terms of the work copyright law. Data were collected using library research techniques. After the research data has been collected, it is processed by elaboration, namely combining the sources of the primary, secondary and tertiary legal materials with deductive and inductive logic. The results of this study indicate that corporate crime is essentially a functional act and is in the form of an inclusion offense. The criminal sanction of imprisonment is 1/3 to the management of the corporation.